The questions of interaction between state and religion and it’s values - Kokeyeva, D. M. (Journal of Oriental Studies, 2016)
in this article raises questions of interaction between state and religion; regulate their activities, learning experiences of other countries on the regulation of interaction between state and religion, their past, present and future is explored.